On the history of the idea of law - Letwin, Shirley Robin (Cambridge University Press, 2005)
The final work of the celebrated conservative thinker Shirley Robin Letwin, On The History of the Idea of Law is the first book ever to collect and criticise the basic theories of law propounded by the great philosophers from Plato to the present.